Econometric analysis of profit efficiency of broiler farms in Ondo state, Nigeria - O. L. Balogun; M. D. Olumide; K. Ayantoye; A. M. Bolarinwa; T. O. Agboola (Diponegoro University, 2023)
Researchers have recently focused their attention on the chicken producers' inability to produce in sufficient quantities and quality, which contributes to the high price of locally produced chickens. The study investigated the profit efficiency of broiler farms in Ondo state, Nigeria. In order to collect cross-sectional data from sixty owners of broiler poultry farms in the study area between October 2021 and January 2022 for the 2021 production year, a multistage survey technique was used. The data were an-alyzed using descriptive statistics, gross margin and Cobb-Douglas stochastic profit frontier model. Average stock size and mortality rate of farmers were 1826 birds and 3.3% respectively while Ross strain of birds was most preferred birds. The result indicated that broiler farming is a lucrative busi-ness with a profitability index of 45.5 %. The results reveal that the cost of feed, cost of labour used and day-old chicks were the variables that significantly explained the profit efficiency of broiler poul-try farms while household size, years of experience and other income source were the profit inefficien-cy variables. The study recommends government supports to broiler farms in form of input subsidies to enhance efficiency